Delayed Instrumentation Following Removal of Cranio-Vertebral Junction Chordomas: A Technical Note - Champagne, Pierre-Olivier; Voormolen, Eduard H.; Mammar, Hamid; Bernat, Anne-Laure; Krichen, Walid; Penet, Nicolas; Froelich, Sébastien (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective To investigate on the feasibility and safety of a new approach which consists of delaying instrumentation after destabilizing craniovertebral junction (CVJ) chordoma surgery, allowing proton beam radiotherapy to be performed in a metal-free tumoral cavity.Design This is a retrospective series of a prospectively maintained database.Participants Five consecutive patients operated on for a CVJ chordomas for which instrumentation after tumor resection was deferred to after radiotherapy treatment.Main Outcome Measures The main outcome consisted of measurements of the following parameters: C0–C2 angle, atlanto-dens interval (ADI), condylar gap, and the position of the dens relative to McGregor's line and coronal inclination, performed at 3 different times for all patients: before tumor surgery (baseline), before instrumentation surgery, and after instrumentation surgery.Results For all patients, CVJ parameters deteriorated during the delay period, but stayed within normal limits for most. Because of radiological instability, one patient necessitated instrumentation before receiving radiotherapy. All parameters except condylar gap were partially corrected after instrumentation. No new neurological symptom or evolving neck pain occurred during the delay period.Conclusion Delayed instrumentation of CVJ chordomas can be a safe alternative that might lead to improved subsequent radiotherapeutical treatment. Patient's selection and close clinical and radiological follow-up are mandatory for the success of this approach.
Keywords: Craniovertebral Junction; chordoma; instability; instrumentation; proton beam therapy